MNE responses in managing FDI amid times of global disruptions - Piirainen, Maria (My University, 2025)
The COVID-19 pandemic, the Russia–Ukraine war and increasing geopolitical tensions as well as energy market disruptions have profoundly affected international business and investment flows. These disruptions have challenged multinational enterprises (MNEs) to reconsider how they manage foreign direct investment (FDI) in an increasingly uncertain global environment. This thesis examines FDI management during global disruptions, with partial attention to European MNEs that have been directly exposed to recent crises. In this thesis I approach the topic by two sub-questions which are how global disruptions challenge firms’ FDI strategies and how management can support firms in responding to these challenges. The research is conducted as a literature-based study, combining theoretical perspectives and recent findings to identify key patterns and strategies in FDI management. The thesis approaches the topic through Dunning’s eclectic (OLI) paradigm to explore how ownership, location and internalization advantages evolve during periods of instability. The findings indicate that disruptions affect FDI by increasing uncertainty, weakening institutional conditions and altering firms’ risk perceptions. Successful management of FDI under such circumstances depends on firms’ ability to anticipate and interpret external risks, maintain strategic resilience and adjust organisational structures. MNEs that diversify markets, strengthen practices and integrate sustainability, digitalization and governance capabilities into their operations are better equipped to handle crises. The thesis highlights that effective FDI management is no longer only about growth but about resilience and long-term stability in an unpredictable world.

COVID-19-pandemia, Venäjän ja Ukrainan välinen sota, kiristyneet geopoliittiset jännitteet sekä energiamarkkinoiden häiriöt ovat vaikuttaneet syvästi kansainväliseen liiketoimintaan ja investointivirtoihin. Näiden häiriöiden seurauksena monikansalliset yritykset (MNE) ovat joutuneet arvioimaan uudelleen, miten ne hallitsevat suorien ulkomaisten investointien (FDI) kokonaisuutta yhä epävarmemmassa globaalissa toimintaympäristössä. Tutkielma tarkastelee FDI:n johtamista globaalien häiriöiden aikana osittain eurooppalaisten yritysten näkökulmasta, sillä ne ovat kohdanneet viime vuosien kriisit poikkeuksellisen voimakkaasti. Tutkimus rakentuu kahden osakysymyksen varaan, jotka tarkastelevat miten globaalit häiriöt haastavat yritysten suorien ulkomaisten investointien strategioita ja millä tavoin johtaminen voi tukea yrityksiä näiden haasteiden ratkaisemisessa. Tutkielma on kirjallisuuskatsaus, joka kokoaa yhteen keskeisiä teoreettisia näkökulmia ja ajankohtaisia tutkimustuloksia suorien ulkomaisten investointien johtamisesta. Löydökset osoittavat, että globaalit häiriöt vaikuttavat suoriin ulkomaisiin investointeihin lisäämällä epävarmuutta, heikentämällä institutionaalista toimintaympäristöä ja muokkaamalla yritysten käsityksiä riskeistä. Monikansalliset yritykset, jotka onnistuvat ennakoimaan riskejä, tulkitsemaan ulkoisen ympäristön signaaleja ja sopeuttamaan organisaation rakenteita tilanteen mukaan, pystyvät säilyttämään ulkomaiset investointinsa vakaampina ja turvaamaan toimintansa jatkuvuuden myös epävarmoina aikoina. Yritykset, jotka hajauttavat toimintaansa, vahvistavat käytäntöjään sekä integroivat vastuullisuuden, digitalisaation ja hyvän hallinnon periaatteita strategiaansa, selviävät paremmin häiriötilanteista. Työ korostaa, että tehokas FDI:n hallinta ei enää tarkoita pelkästään kasvua, vaan myös pitkäjänteistä vakautta, sopeutumiskykyä ja ennakoimista ennakoimattomassa maailmassa.
Keywords: foreign direct investment, multinational enterprises, global disruption, OLI paradigm, resilience, competitiveness, risk management